Mixed-Race Politics and Neoliberal Multiculturalism in South Korean Media - Ahn, Ji-Hyun (East Asian Popular Culture, 2018)
This book studies how the increase of visual representation of mixed-race Koreans formulates a particular racial project in contemporary South Korean media. It explores the moments of ruptures and disjuncture that biracial bodies bring to the formation of neoliberal multiculturalism, a South Korean national racial project that re-aligns racial lines under the nation's neoliberal transformation. Specifically, Ji-Hyun Ahn examines four televised racial moments that demonstrate particular aspects of neoliberal multiculturalism by demanding distinct ways of re-imagining what it means to be Korean in the contemporary era of globalization. Taking a critical media/cultural studies approach, Ahn engages with materials from archives, the popular press, policy documents, television commercials, and television programs as an inter-textual network that actively negotiates and formulates a new racialized national identity. In doing so, the book provides a rich analysis of the ongoing struggle over racial reconfiguration in South Korean popular media, advancing an emerging scholarly discussion on race as a leading factor of social change in South Korea.